Prostate cancer screening: Continued controversies and novel biomarker advancements. (31st December 2022) - Tidd-Johnson, Atiyah; Sebastian, Sneha Annie; Co, Edzel Lorraine; Afaq, Munaza; Kochhar, Hansini; Sheikh, Mona; Mago, Arpit; Poudel, Sujan; Fernandez, John A.; Rodriguez, Ivan D.; Razdan, Sanjay
Abstract: Prostate cancer (PCa) screening remains one of the most controversial topics in clinical and public health. Despite being the second most common cancer in men worldwide, recommendations for screening using prostate-specific antigen (PSA) are unclear. Early detection and the resulting postscreening treatment lead to overdiagnosis and overtreatment of otherwise indolent cases. In addition, several unwanted harms are associated with PCa screening process. This literature review focuses on the limitations of PSA-specific PCa screening, reasons behind the screening controversy, and the novel biomarkers and advanced innovative methodologies that improve the limitations of traditional screening using PSA. With the verdict of whether or not to screen not yet unanimous, we hope to aid in resolution of the long-standing debate.